COMPORTAMENTO INGESTIVO DE BOVINOS DE CORTE EM PASTEJO RECEBENDO UM ADITIVO FITOTERAPICO OU MONENSINA. - TEIXEIRA, Edvan Correia,; SILVA, Gislaine Jara,; SILVA, Camila de Souza,; SANTOS, Marrony Gonçalves Pires,; FERNANDES, Henrique Jorge, (ANAIS DO ENIC, 2024)
-